2011
DOI: 10.1371/journal.pgen.1002004
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Genome-Wide Association Studies in Celiac Disease and Rheumatoid Arthritis Identifies Fourteen Non-HLA Shared Loci

Abstract: Epidemiology and candidate gene studies indicate a shared genetic basis for celiac disease (CD) and rheumatoid arthritis (RA), but the extent of this sharing has not been systematically explored. Previous studies demonstrate that 6 of the established non-HLA CD and RA risk loci (out of 26 loci for each disease) are shared between both diseases. We hypothesized that there are additional shared risk alleles and that combining genome-wide association study (GWAS) data from each disease would increase power to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(184 citation statements)
references
References 43 publications
9
161
1
4
Order By: Relevance
“…Multiple markers in the vicinity of UBE2L3 have previously been shown to be associated with immunological diseases such as CelD, rheumatoid arthritis and CD. 10,11 Despite of the association of this region with multiple diseases, the role of the YDJC gene is currently largely unknown. UBE2L3 participates in ubiquitylation and has a key role in the regulation of innate and adaptive immune systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple markers in the vicinity of UBE2L3 have previously been shown to be associated with immunological diseases such as CelD, rheumatoid arthritis and CD. 10,11 Despite of the association of this region with multiple diseases, the role of the YDJC gene is currently largely unknown. UBE2L3 participates in ubiquitylation and has a key role in the regulation of innate and adaptive immune systems.…”
Section: Resultsmentioning
confidence: 99%
“…8 A subset of these CelD risk loci may also be associated with increased risk for other autoimmune diseases, including IBD. 9,10 In this study, we investigated systematically whether any of the CelD risk loci highlighted by Dubois et al 8 also affect susceptibility to IBD in the Finnish population. A meta-analysis in a combined Finnish and Swedish UC data set was also performed.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions share with CD an association with risk haplotypes HLA-DQ2 and HLA-DQ8 (Ch'ng et al 2007;Pham Short et al 2012). In addition to T1DM, shared (non-HLA) genetic risk factors with CD have been noted for Crohn's disease (CrD) (Festen et al 2011) and rheumatoid arthritis (RA) (Zhernakova et al 2011). …”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%
“…Importantly, this study also demonstrated that nearly 50% of CD risk SNPs are in close proximity to expression quantitative trait loci (eQTLs), suggesting a likely role for changes in levels of gene expression in CD. As mentioned above, additional GWA studies have identified risk loci shared between CD and other autoimmune conditions such as T1DM, RA, CrD, and ulcerative colitis (UC) (Zhernakova et al 2007(Zhernakova et al , 2011Smyth et al 2008;Barrett et al 2009;Festen et al 2009Festen et al , 2011Cotsapas et al 2011;Gutierrez-Achury et al 2011). These studies have illuminated the tremendously pleiotropic nature of loci underlying autoimmune and other immune related conditions.…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%
“…As collecting many more samples for each disease will form a bottleneck for performing new genetic studies, combining data sets for different diseases may be the way forwards for finding new shared genetic loci. Recently, the first cross-disease (including CD) metaanalyses of GWA studies were successfully performed [75,76]. A study in which GWA analyses of CD and RA were combined revealed eight new shared loci for these two diseases, in addition to the six that were already known.…”
Section: Future Perspectivesmentioning
confidence: 99%